QUALITY OF SERVICE AND PRICE ON CUSTOMER SATISFACTION Coffee Shop in BANDUNG CITY (Case Study on Bandung City Coffee Shop Customers) - Rusmin Nuryadin; Lucy Nurfadilah; Ine Aprianti (SEAN Institute, 2023)
Marketing is a part that has a very important role, and cannot be separated from human life. Service can basically be said as an action and treatment or way of serving other people to fulfill their needs and desires. The level of customer satisfaction with a service can be measured by comparing consumer expectations of the desired service quality with the reality that is received and felt. This research is to look at gaps. The samples taken were 100 respondents. Data measurement was carried out by distributing questionnaires using an ordinal scale. The analysis technique used is validity test, reliability test, classic assumption test, multiple linear analysis, correlation, determination, t test and F test. The results of this study indicate that the results of the analysis show that the variable service quality (X1) has a coefficient of determination of 46.% on customer satisfaction (Y), meaning that if the quality of service is getting better, then customer satisfaction will increase. The value of tcount (5.435) > ttable (2.00758). The results of the analysis show that the price variable (X2) has a coefficient of determination of 32.7% on consumer satisfaction (Y), meaning that if the price is in accordance with consumer wishes, consumer satisfaction will increase . And the value of tcount (3.963) > ttable (2.00758). The results of the analysis of the coefficient of determination obtained 79.5%, Fcount (96.934) > Ftable (3.18). So, service quality (X1) and price (X2) together affect customer satisfaction (Y) at cafe infinito.